Efeito sinérgico entre a terapia fotodinâmica e a cisplatina: uma nova abordagem para o câncer de colo uterino - Freitas, Laura Marise de [UNESP] (2015)
Cervical cancer is a malignant tumor that has HPV infection as the main risk factor for its emergence. Current therapies for the treatment of cervical cancer have as major disadvantage substantial excision of cervical stroma and many adverse effects associated with chemotherapy, especially cisplatin. In this scenario, photodynamic therapy (PDT) has proven to be a promising alternative, specially if combined with conventional treatments. The technique is based on the administration of a non-toxic photosensitizing agent to the patient with subsequent exposure to a light source of a specific wavelength, resulting in cytotoxic response by oxidative damage. Thus, the present study intended to evaluate in vitro cytotoxicity, the type of induced death and the genotoxic and mutagenic effects of PDT alone and associated with cisplatin on the cell lines SiHa, C-33 A and HaCaT, using the photosensitizers Photogem and methylene blue. It was observed that both the photodynamic therapy mediated by methylene blue (MBPDT) and Photogem mediated therapy (PGPDT) were effective in reducing cell viability with cytotoxicity being dependent on the light dose. Cisplatin was less effective over the three lines compared to PDT. However, the combination cisplatin + PDT had a greater synergistic effect and caused greater cell death in all conditions tested. The sequence of treatment application (PDT + cisplatin or cisplatin + PDT) was important and depended on the photosensitizer. Regarding the type of induced cell death, both AMPDT and PGPDT induced caspase-independent death, but AMPDT induced the typical morphology of necrosis, while PGPDT induced morphology was most similar to apoptosis. Cisplatin predominantly induced apoptosis; and combination therapy induced greater apoptosis- or necrosis-like rate according to the cell line, but always with a higher percentage of dead cells than monotherapies. MBPDT, either as monotherapy or in combination with cisplatin was ...